2015
DOI: 10.1002/cne.23706
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of pacemaker neurons in the neonatal rat superficial dorsal horn

Abstract: Pacemaker neurons with an intrinsic ability to generate rhythmic burst-firing have been characterized in lamina I of the neonatal spinal cord, where they are innervated by high-threshold sensory afferents. However, little is known about the output of these pacemakers, as the neuronal populations which are targeted by pacemaker axons have yet to be identified. The present study combines patch clamp recordings in the intact neonatal rat spinal cord with tract-tracing to demonstrate that lamina I pacemaker neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…Horizontal spinal cord slices, in contrast to coronal or parasagittal slices, offer the unique advantage that afferent fibers, dorsal horn neurons, and dorsal spinal circuits are preserved virtually intact. In horizontal slices, lamina I neurons were visualized through the white matter using infrared light-emitting diode (IR-LED) illumination (Safronov et al, 2007;Szucs et al, 2009;Li et al, 2015b), a CCD video camera (Oly 150; Olympus), and a 40ϫ water-immersion objective mounted on an upright microscope (BX51WI; Olympus). At P18 -P27, the postnatal Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Horizontal spinal cord slices, in contrast to coronal or parasagittal slices, offer the unique advantage that afferent fibers, dorsal horn neurons, and dorsal spinal circuits are preserved virtually intact. In horizontal slices, lamina I neurons were visualized through the white matter using infrared light-emitting diode (IR-LED) illumination (Safronov et al, 2007;Szucs et al, 2009;Li et al, 2015b), a CCD video camera (Oly 150; Olympus), and a 40ϫ water-immersion objective mounted on an upright microscope (BX51WI; Olympus). At P18 -P27, the postnatal Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue preparation was performed as previously described (Li et al, 2015). Briefly, DiI injected Sprague-Dawley rats, on P3–P5, were put under a deep plane of anesthesia with sodium pentobarbital (30 mg/kg; Fatal-Plus, Vortec Pharmaceuticals, Dearborn, MI).…”
Section: Methodsmentioning
confidence: 99%
“…Oscillatory neurons are ubiquitous in the basal ganglia, and include dopaminergic neurons in the mesencephalon, tonically active cholinergic neurons in the striatum, as well as the principal neurons in the output nuclei, including the globus pallidus and the substantia nigra par reticulata (Surmeier et al 2005). Pacemakers have also been identified in the inferior olive (Lang 2001), the pons (Williams and Marshall 1987), and the neonatal spinal cord (Li et al 2015). It has been suggested that hippocampal pyramidal neurons may act as autonomous pacemakers under certain conditions in vivo (Yamada-Hanff and Bean 2013).…”
Section: Discussionmentioning
confidence: 99%